Pengaruh Hemolisis Terdapat Kadar Serum Glutamate Pyruvate Transaminase (SGPT) Sebagai Salah Satu Parameter Fungsi Hati - hartono kahar (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2017)
AbstractSGPT examination is one of the important checks on the state of a particular patient, for example, in patients with liver disease, hepatitis, and so forth. The other purpose is to detect the presence of liver damage. So there was an effect in the event of an increase in maupaun drop in levels. And the serum circumstances that do not qualify, such as serum hemolysis, will greatly affect the actual levels of ALT. Based on the research background, the authors formulate the problem as follows: "Is there any effect of hemolysis on SGPT levels as one of the parameters of liver function?". The purpose of this study is to prove whether there is an influence of hemolysis on SGPT levels as one of the parameters of liver function. The sample was 20 samples and 20 samples of hemolysis hemolysis. Location and time of the research conducted at Muhammadiyah Hospital Clinical Laboratory Lamongan ie in January and July. Of the 20 samples analyzed, showing that levels higher than the hemolysis ALT SGPT levels no hemolysis. When the serum through lysis will experience a significant increase. To test the effect of hemolysis on SGPT levels paired t test was used because the data from this study with normally distributed. The results of a paired t test analysis between serum hemolysis and no hemolysis on levels of serum ALT levels showed a significant value 0.00 thus P <0.05 it can be concluded that there is no difference between the levels of ALT SGPT levels of hemolysis with hemolysis. That means there is the influence of hemolysis on SGPT levels as one of the parameters of liver function. Key word : hemolysis, glutamate pyruvate transminase